Endogenous technology adoption and household food security: the case of improved cowpea varieties in northern Nigeria - Alene, A.; Manyong, Victor M. (2006)
Impact studies assuming exogenous technology adoption are bound to overstate or understate the true impact of improved agricultural technologies, especially in situations where agricultural technologies are targeted to, or adopted by, a certain group of farmers. This paper examined the impact of improved cowpea varieties on household food security in northern Nigeria using the method of instrumental variables to account for endogenous technology adoption. We found that adopters of improved cowpea varieties were more food-secure than non-adopters. The results further showed that social capital and the intensity of cultivation of soybean had a positive and significant impact. Supply of improved seeds and access to markets and extension services are important factors conditioning the rate of adoption and hence the contribution of improved cowpea varieties to food security in northern Nigeria.